SEX PREFERENCE ON CHILD AND MODERN CONTRACEPTION USE IN FERTILE AGE WOMEN IN INDONESIA (ANALYSIS OF IDHS 2017) - Deby Novita Sari (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2020)
Generally, this study aims to describe the characacteristics of modern contraception users in fertile age women in Indonesia. Specifically, this study will examine the effect of the children's sex preferences on the use of modern contraception. Furthermore, the control variables used are age, education taken by the mothers, mothers' working status, marital status, Family Planning Field Officer (Petugas Lapangan Keluarga Berencana/PLKB) visits, and internet usage. The data used in this study was taken from the results of the Indonesian Demographic and Health Survey (IDHS) 2017. Data analysis was using descriptive and inferential analysis. Descriptive analysis used is in the form of a single table and a cross-tabulation, while the inferential analysis used is binary logistic regression. Based on the descriptive analysis results, it can be concluded that 79.35% of fertile age women (15-49 years old) in Indonesia do not have particular sex preference on their children. Moreover, the inferential analysis results with a significance level by 1%, it appears that child's sex preference will reduce the chance of modern contraception use. Women's age, the number of children that safely delivered, marital status, and FPFO visits are having the positive effect on the modern contraception use, while the residential area, education taken, and internet usage are negatively affect the modern contraception use.